Commemorating history, historicising commemoration: Easter Rising centenary in Ireland from editorial and typographical perspectives - Koneczniak, Grzegorz (Theoria et Historia Scientiarum, 2024)
This essay offers a combination of historical, editorial and commemorative approaches to the process of historicising the practices of remembering the Easter Rising in Ireland. Considered one of the most defining historical moments that has shaped the present-day Ireland and its relationships with Great Britain, the Easter Rebellion of 1916 was remembered in a series of events comprised within the framework of the “Decade of Centenaries” programme of celebrations. The history of the Easter Rising, spoken and unspoken, was symbolically re-enacted in various commemorative forms and via multiple media: television, radio, theatre, internet and many more cultural institutions. The study deals with crucial interconnected problems concerning the ephemerality of commemoration treated as a historical moment whose aim is to remember the defining historical event and which, paradoxically, itself becomes history. The importance of editorial and typographical considerations, as studied on the basis of selected commemorative texts and media, are important in the way in which commemoration functions and seeks unity in terms of shaping the perceptions of historical events in Ireland. Yet, the editorial, typographic and graphic dimensions of such texts may also question the discourse of practices or, at least, signal inconsistencies. The methodology applied here is that of a case study and comparative examination. Following the temporal confrontative procedure employed in one of the previous coauthored articles (see Koneczniak & Koneczniak, 2022), the research cases involve two historical moments: the analysis conducted and described during the exact commemorative moment, that is, the precise one hundredth anniversary of the Easter Rising, and the state found almost five years after the remembrance series, at the beginning of 2021. The comparative basis involves the same research materials, and it focuses on determining changes in the access to the original commemorative materials available in 2016 and linked to the celebration of the 1916 Rising.